Performance Analysis of Gravity-Driven Oil-Water Separation Using Membranes with Special Wettability - Oh, Seungtae (Langmuir : the ACS journal of surfaces and colloids, 2019)
A membrane with selective wettability to either oil or water has been utilized for highly efficient, environmentally friendly membrane-based oil-water separation. However, a predictive model, which can be used to evaluate the overall separation performance of the membrane, still needs further development. Herein, we investigate three separation performance parameters, that is, separation efficiency, liquid intrusion pressure, and mass flux in particular, as a function of pore geometry and liquid properties using metallic meshes whose surface wettability is modified by scalable spray coating. We show that the prepared membrane exhibits a separation efficiency over 98% below the intrusion pressure, while the intrusion pressure increases with the decrease of pore size of the membrane. Particularly, we develop a semi-empirical model for the mass flux through the membrane. As application examples of our performance analysis, we successfully predict the separation time for one-way and two-way gravity-driven separation of the oil-water mixture, the decrease of the mass flux due to membrane fouling, and the maximum allowable separation capacity of the given membrane. This work can help to design optimal membrane-based oil-water separation systems for actual industrial applications by providing a selection guideline for separation membranes